Bentuk-Bentuk Kesalahan Fonologi dalam Membaca Teks Arab Siswa Kelas VIII di MTs Negeri 1 Kota Gorontalo - Paputungan, Mardhatillah; Noor, Damhuri Dj.; Miolo, Mukhtar I (Universitas Muhammadiyah Gorontalo, 2023)
Students who will learn Arabic have different abilities. Likewise, in terms of pronouncing the sounds of Arabic sentences, if there is an error, it will impact the meaning contained in the sentence. The purpose of this study is to find out how the forms of phonological errors that occur in Class VIII students of MTs Negeri 1 Gorontalo City in the 2023-2024 school year, this research is a type of research using the Anakes method (Error Analysis) using a Descriptive Qualitative approach, the data collection technique is by Oral Test, and Sound Recording, while the data analysis technique uses the Ellis technique based on language error analysis using the Anakes procedure. The results of the forms of phonological errors in reading Arabic texts that researchers get in the field are students who find it challenging to pronounce Makhoriul letters by the nature of the letters so that letter swapping occurs, such as errors in swapping letters ع read أ, ذ readز, ظ is read,ز ث is read,س ض is read,د ح is read,ه and learners who have difficulty distinguishing the pronunciation of letters that are almost the same as the error أَبْدَأُ is read أَبْدَعُ, إِذَنْ is read إِزَنْ ثُمَّ is read سُمَّ, رِحْلَةٌ is read رِهْلَةٌ.